PROBLEMATIKA PEMBELAJARAN BACA TULIS AL-QUR’AN PADA MATA PELAJARAN AL-QUR’AN HADITS KELAS RENDAH DI MI HIDAYATUL MUBTADIIN TASIKMADU MALANG - Dewi Etika Suri; Anwar Sa'dullah; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
This study is to find out the learning problems that exist in MI Hidayatul Mubtadiin Tasikmadu Malang, which is about the problem of literacy in the Qur'an on the subjects of the Al-Hadith in the lower class I. II. And III. This research was conducted using observation, interviews, and documentation. In this study the researcher used an interview instrument which was arranged in order to get the results of the interview. Studying the Hadith Qur'an is the most important subject matter in order to enter the gates of knowledge related to Islam, especially in Madrasah Ibtidaiyah institutions. Therefore, as a teacher must be able to apply effective and efficient learning so that students are easier to read and write the Qur'an. However, the teacher cannot implement it because teachers do not understand the problems that arise from the methods, media or characteristics of their students. In this case the researcher will discuss about low-grade Qur'anic literacy learning in MI Hidayatul Mubtadiin Tasikmadu Malang, the problems experienced by teachers in low-grade Qur'anic literacy learning and the problems faced by students in learning to read and write Al- Low-grade Qur'an in Tasikmadu Malang Hidayatul Mubtadiin MI.Keywords: Problems, Reading and Writing the Qur'an.